Third Trimester Equivalent Alcohol Exposure Reduces Modulation of Glutamatergic Synaptic Transmission by 5-HT1A Receptors in the Rat Hippocampal CA3 Region - Morton, Russell A.; Valenzuela, C. Fernando (Frontiers in Neuroscience, 2016)
Fetal alcohol exposure has been associated with many neuropsychiatric disorders that have been linked to altered serotonin (5-hydroxytryptamine; 5-HT) signaling, including depression and anxiety. During the first two weeks of postnatal life in rodents (equivalent to the third trimester of human pregnancy) 5-HT neurons undergo significant functional maturation and their axons reach target regions in the forebrain (e.g. cortex and hippocampus). The objective of this study was to identify the effects of third trimester ethanol (EtOH) exposure on hippocampal 5-HT signaling. Using EtOH vapor inhalation chambers, we exposed rat pups to EtOH for 4 hours/day from postnatal day (P) 2 to P12. The average serum EtOH concentration in the pups was 0.13 ± 0.04 g/dl (legal intoxication limit in humans = 0.08 g/dl). We used brain slices to assess the modulatory actions of 5-HT on field excitatory postsynaptic potentials in the hippocampal CA3 region at P13-P15. Application of the GABAA/glycine receptor antagonist, picrotoxin, caused broadening of field excitatory postsynaptic potentials (fEPSPs), an effect that was reversed by application of 5-HT in slices from air exposed rats. However, this effect of 5-HT was absent in EtOH exposed animals. In slices from naïve animals, application of a 5-HT1A receptor antagonist blocked the effect of 5-HT on the fEPSPs recorded in presence of picrotoxin, suggesting that third trimester ethanol exposure acts by inhibiting the function of these receptors. Studies indicate that 5-HT1A receptors play a critical role in the development of hippocampal circuits. Therefore, inhibition of these receptors by third trimester ethanol exposure could contribute to the pathophysiology of fetal alcohol spectrum disorders.